2018
DOI: 10.1063/1.5008873
|View full text |Cite
|
Sign up to set email alerts
|

Effects of optical attenuation, heat diffusion, and acoustic coherence in photoacoustic signals produced by nanoparticles

Abstract: Behavior of the photoacoustic signal produced by nanoparticles as a function of their concentration was studied in detail. As the concentration of nanoparticles is increased in a sample, the peak-to-peak photoacoustic amplitude increases linearly up to a certain value, after which an asymptotic saturated behavior is observed. To elucidate the mechanisms responsible for these observations, we evaluate the effects of nanoparticles concentration, the optical attenuation and the effects of heat propagation from na… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…This will be investigated in the next section. The velocity potential equation, (22), is solved for each medium with appropriate initial and boundary conditions. Zero velocity and acceleration are used for initial conditions, yielding zero velocity potential and its derivative at time t ¼ 0, i. e.,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This will be investigated in the next section. The velocity potential equation, (22), is solved for each medium with appropriate initial and boundary conditions. Zero velocity and acceleration are used for initial conditions, yielding zero velocity potential and its derivative at time t ¼ 0, i. e.,…”
Section: Resultsmentioning
confidence: 99%
“…Analogous to the temperature solution, the solution of the velocity potential equation with the initial and boundary conditions, Eqs. (22) and (25d), is sought by first writing the equations in a dimensionless form using a change of variable to a dimensionless velocity potential as…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above-described approaches are valid until non-linearities arise in the laser / PNP interaction, thereby influencing the photoacoustic signal [ 61 ]. This possibility has been described both theoretically [ 65 , 66 ] and experimentally [ 58 , 60 , [67] , [68] , [69] ]. Several adjustable experimental conditions determine signal non-linearities, including the laser pulse characteristics and PNP concentration.…”
Section: Photoacoustic Response Of Nanomaterialsmentioning
confidence: 99%
“…Comprehensive theoretical studies on photoacoustic generation have been reported in the literature . And recent theoretical studies can be found elsewhere …”
Section: Photoacoustic Generation—mechanism and General Considerationsmentioning
confidence: 99%